2020
DOI: 10.1029/2019ea000740
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Various Machine Learning‐Based Bias Correction Methods for Numerical Weather Prediction Model Forecasts of Extreme Air Temperatures in Urban Areas

Abstract: Forecasts of maximum and minimum air temperatures are essential to mitigate the damage of extreme weather events such as heat waves and tropical nights. The Numerical Weather Prediction (NWP) model has been widely used for forecasting air temperature, but generally it has a systematic bias due to its coarse grid resolution and lack of parametrizations. This study used random forest (RF), support vector regression (SVR), artificial neural network (ANN) and a multi-model ensemble (MME) to correct the Local Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 79 publications
(97 reference statements)
3
66
0
1
Order By: Relevance
“…While experiments in this paper were developed and tested in an image classification application context, an experiment was conducted to understand if the proposed approach would also work in a regression context. A recently collated temperature prediction data set [ 32 ] was used to test if the proposed approach could train neural network models for regression problems. The paper uses two identification attributes (station and time), fourteen numerical weather prediction model attributes, two in situ temperature observations and five geographical attributes to forecast maximum and minimum next-day temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While experiments in this paper were developed and tested in an image classification application context, an experiment was conducted to understand if the proposed approach would also work in a regression context. A recently collated temperature prediction data set [ 32 ] was used to test if the proposed approach could train neural network models for regression problems. The paper uses two identification attributes (station and time), fourteen numerical weather prediction model attributes, two in situ temperature observations and five geographical attributes to forecast maximum and minimum next-day temperatures.…”
Section: Discussionmentioning
confidence: 99%
“… Results of the application of the proposed approach to a temperature prediction (regression problem) data set [ 32 ]. The proposed approach produced a competitive Mean Absolute Error (MAE) of 1.32 C in comparison to the best alternative approach (Adam) which produced an MAE of 0.97 C. Reported numbers are best outcomes of three random seed runs.…”
Section: Figurementioning
confidence: 99%
“…where, z /2 is the quantile satisfying P(N(0, 1) ≥ z /2 ) = /2, and̂2 M is the direct-plug-in estimator of the asymptotic variance 2 . The expression of̂2 M is given as follows.…”
Section: Moreover We Havementioning
confidence: 99%
“…To solve this problem, a deep learning-based refinement model was proposed in [ 7 ], and the prediction model using the refined data provided better prediction accuracy than the model using data approximated using linear interpolation. The accuracy of future weather prediction can also be increased by augmenting the data using satellite information or combining a variety of types of information [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it should be assumed for the prediction model that all AWS data should include no errors or missed data, which is a situation that is not guaranteed in practice. Recently, there have been several studies indicating that combining numerical forecast data with observed data improved the accuracy of temperature prediction [ 9 ] and aerosol prediction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%